Endophytic pestalotiod taxa in Dendrobium orchids - Ma, Xiao-Ya; Maharachchikumbura, Sajeewa S.n.; Chen, Bao-Wen; Hyde, Kevin D.; Mckenzie, Eric H.c.; Chomnunti, Putarak; Kang, Ji-Chuan (Phytotaxa, 2019)
Pestalotiod taxa commonly occur in plants as endophytes, pathogens or saprobes. Endophytic Pestalotiopsis and Neopestalotiopsis species were isolated from Dendrobium cariniferum, D. loddigesii and two unidentified orchid species sampled in southwestern China and northern Thailand. Morphological and molecular comparison identified the isolates as two new species; Neopestalotiopsis dendrobii, and Pestalotiopsis doitungensis; two existing species P. lushanensis and P. trachicarpicola. This is the first report of Neopestalotiopsis isolated from the orchid genus Dendrobium and is the first report of pestalotiod fungi in D. careniferum. Pestalotiopsis lushanensis and P. trachicarpicola are new recorded fungal endophytes in Dendrobium orchids.